Litterær erfaring og dialogisme - Hans Lauge Hansen (Museum Tusculanum Press, 2006)
In this book the author reflects on the role of the reading of literature in the cultural processes of identity formation. The book forms an argument for the contention that the aesthetic approach to literary texts is not in opposition to a culture-analytical orientation but actually constitutes a prerequisite for it. Moreover, the development of the general semiotic theory proposes a strengthening of interdisciplinary work as regards i.e. visual impressions, linguistic problems and historical issues. The target group of the book comprises teachers and students of foreign language studies at the advanced education centres.